THE IMPORTANCE OF FINANCIAL TECHNOLOGY AS A MECHANISM TO ENHANCE THE FINANCIAL PERFORMANCE OF ISLAMIC BANKS: AL-SALAM BANK AS A CASE STUDY - Saber Bouaouina, (International Journal of Innovative Technologies in Social Science, 2024)
This research paper aims to demonstrate the effectiveness of financial technology (FinTech) in enhancing the financial performance of Islamic banks through an analytical case study of Al-Salam Bank – Algeria, relying on the bank’s annual reports over the period 2019–2022.The study has concluded with the result that the bank faces a necessity to adopt financial technology within its operational framework, as FinTech constitutes one of the most critical financial solutions that contribute to improve its financial performance. Furthermore, FinTech offers integrated tools and solutions that enhance user experience and deliver innovative banking services to customers, so that strengthening the bank’s competitive capacity.